Solid-state lithium-ion batteries containing nanoporous silicon anodes
A silicon anode with columnar structures and argyrodite sulfide electrolyte improves the stability and performance of solid-state lithium-ion batteries by addressing interface issues and swelling, resulting in enhanced cycle life and efficiency.
Patent Information
- Application Number
- JP2024538205
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-23
- Filing Date
- 2022-12-22
- Publication Date
- 2025-01-22
AI Technical Summary
Existing solid-state lithium-ion batteries face challenges with electrode/electrolyte interfaces that lead to lithium ion loss and structural integrity issues due to swelling, limiting cycle life and performance.
A silicon anode composed of an amorphous porous silicon film with columnar structures on a current collector, combined with an argyrodite sulfide-based solid electrolyte and a cathode layer, is used to form a stable solid-state battery structure.
The solution enhances cycle life and cycling performance by stabilizing the electrode interface, reducing lithium ion loss, and preventing structural failure during battery operation.
Smart Images

Figure 2025501605000001 
Figure 2025501605000002 
Figure 2025501605000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to lithium-ion batteries, and more particularly to solid-state lithium-ion batteries including silicon anodes. [Background technology]
[0002] In recent years, as communication devices such as personal computers, video cameras, and mobile phones continue to become more popular, high-density rechargeable lithium-ion batteries are now common in all kinds of electronic devices. Despite their widespread use, scientists believe that traditional Li-ion liquid electrolyte battery technology is already approaching its full potential and that new types of batteries are needed. Furthermore, currently commercially available lithium-ion batteries typically use organic electrolyte solutions that contain solvents that are combustible, flammable, and often toxic. Thus, there are safety and operating temperature concerns regarding the use of lithium-ion batteries.
[0003] More recently, there has been significant interest in solid-state lithium-ion batteries, in which a solid or semi-solid electrolyte layer is used instead of an electrolyte solution and does not contain flammable organic solvents. Solid-state batteries are very similar to lithium-ion liquid electrolyte batteries, with the main difference being the use of a solid or semi-solid electrolyte instead of a liquid electrolyte.
[0004] Solid electrolytes known to date include organic and inorganic materials, such as oxides, sulfides, phosphates, polyethers, polyesters, nitriles, polysiloxanes, polyurethanes, and materials such as glass, ceramics, etc., can be used for this purpose. The performance of the battery depends on the type of electrolyte used, for example ceramics are more suitable for rigid battery systems due to their high elastic modulus, while the low elastic modulus of polymers makes them suitable for flexible devices. More recently, sulfide-based solid electrolyte materials have been described, for example in US2020 / 0087155A1 and US2021 / 0143413A1. Silicon anodes with various morphologies have also been disclosed, for example silicon nanowires are shown in EP3876311.
[0005] However, one of the main obstacles limiting the improvement of lithium-based battery performance is the electrode / electrolyte interface, which is key to battery performance since it is the place where electrons and Li ions bind and then become stored in the electrode via intercalation, alloying, or simply as Li metal. Known solid electrolyte and electrode material combinations are prone to losing lithium ions during cycling as new solid electrolyte interfaces are spontaneously formed. Furthermore, known anode materials are prone to swelling during battery operation, which ultimately results in loss of structural integrity. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] US2020 / 0087155A1 [Patent Document 2] US2021 / 0143413A1 [Patent Document 3] EP3876311 [Non-patent literature]
[0007] [Non-Patent Document 1] Barrett, EP; Joyner, LG; Halenda, PP (1951), "The Determination of Pore Volume and Area Distributions in Porous Substances. I. Computations from Nitrogen Isotherms", Journal of the American Chemical Society, 73(1): 373~380 [Non-Patent Document 2] Brunauer, S.; Emmett, PH; Teller, E. (1938), "Adsorption of Gases in Multimolecular Layers", Journal of the American Chemical Society, 60(2): 309~319 Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, it would be desirable to have a battery composition that mitigates one or more of the obstacles to solid-state battery performance. Still further, there is a need for solid-state batteries that include improved electrode materials with increased cycle life and / or cycling performance. [Means for solving the problem]
[0009] Thus, the present disclosure provides: (i) a silicon anode comprising an essentially pure amorphous porous silicon film deposited on a current collector and comprising a plurality of columnar structures; (ii) an electrolyte layer comprising one or more solid components; (iii) a cathode layer comprising a cathode active material; and The present invention relates to a lithium-ion battery, including
[0010] In a second aspect, the present disclosure further relates to a method for assembling a solid or semi-solid battery based on the use of a silicon anode, comprising: (i) homogeneously distributing an argyrodite sulfide based solid electrolyte powder on a silicon anode layer and compressing under pressure; (ii) homogeneously distributing a cathode mix powder on top of the layer formed in the previous step, after which (iii) placing an aluminum current collector on top of the cathode mix powder; and (iv) applying pressure to compress all the battery materials to form a solid state battery.
[0011] The present disclosure also relates to a method for assembling a multi-layered solid state battery, comprising: (i) homogenously distributing an argyrodite sulfide-based electrolyte powder on a silicon anode layer; (ii) homogenously distributing a cathode mix powder on the sulfide-based electrolyte powder; (iii) disposing an aluminum current collector on the cathode mix powder; (iv) homogenously distributing the argyrodite sulfide-based solid electrolyte powder on the cathode mix powder and then homogenously distributing the cathode mix powder on the other side of the aluminum current collector; (v) depositing a double-sided deposited silicon anode on the argyrodite sulfide-based solid electrolyte powder; and (vi) repeating steps (ii)-(v) and (iv) and finally applying pressure to compress the above components including the electrolyte powder and the silicon anode layer to form a multi-layered solid state battery.
[0012] Yet another object is to provide a battery comprising an electrolyte, a cathode, a separator and a composite material according to the invention or obtainable according to the method according to the invention.
[0013] In another aspect, the present invention provides the use of a composite material according to the invention or obtainable according to the method according to the invention in a battery or for manufacturing a battery.
[0014] In another aspect, the present invention relates to an anode material for use in a battery, preferably a solid-state battery, comprising: (i) a silicon anode comprising an essentially pure amorphous porous silicon film deposited on a current collector and comprising a plurality of columnar structures, the plurality of columnar structures being frustoconical shaped structures converging from and diverging upwardly from a closed anchoring point at a basal surface, with an average cone angle α in the range of 65° to 85°, preferably 70° to 80°.
[0015] The present disclosure may be understood with respect to the present invention by reference to the following figures: The illustrative figures should not be considered limiting, but instead for purposes of explanation and understanding. [Brief description of the drawings]
[0016] [Figure 1A] 1 is a diagram showing a cross section of an embodiment of a single-sided silicon anode in an all-solid-state battery. In FIG. A, item 1 represents a copper foil as an anode current collector, item 2 represents a silicon film, item 3 represents a solid electrolyte layer, item 4 represents a cathode mixture layer, and item 5 represents a cathode current collector, which may typically be an aluminum foil. Items 1 and 2 should be considered as units in the present invention. [Figure 1B] 1A is a cross-sectional view of an embodiment of a double-sided silicon anode in an all-solid-state battery, in which units 1 to 5 are the same as those in FIG. [Figure 2A] FIG. 1 shows an example of the top of a single-sided deposited silicon anode. [Figure 2B] FIG. 1 shows an example of a cross-sectional SEM image of a single-sided deposited silicon anode. [Figure 2C]Figures 1A-1C show examples of cross-sectional SEM images of double-sided deposited silicon anodes. Noteworthy in all figures are columnar structures that may include essentially parallel columnar structures, but may be arranged such that an angle is formed between the basal plane and the central axis of the columns. Such shapes are also typically referred to as stacked cones, ice cream cones, or stacked cone structures. The diameter of such stacked cones and / or ice cream cones can range from 1 to 10 μm. Despite these structural variations, many types of silicone anode materials are suitable for use in the compositions of the present invention. [Figure 3A] 3A, 3B, 3C, and 3D show three examples of electrochemical rate performance of single-sided silicon anodes with various mass loadings in solid-state half-cells. Argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer, and lithium and indium metal foils are used as the counter electrodes. In these Figures 3A, 3B, 3C, and 3D, the rate performance is shown for Si anodes with various mass loadings, and 1C rate is defined as 3000mAh / g relative to the Si mass. [Figure 3B] 3A, 3B, 3C, and 3D show three examples of electrochemical rate performance of single-sided silicon anodes with various mass loadings in solid-state half-cells. Argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer, and lithium and indium metal foils are used as the counter electrodes. In these Figures 3A, 3B, 3C, and 3D, the rate performance is shown for Si anodes with various mass loadings, and 1C rate is defined as 3000mAh / g relative to the Si mass. [Figure 3C] 3A, 3B, 3C, and 3D show three examples of electrochemical rate performance of single-sided silicon anodes with various mass loadings in solid-state half-cells. Argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer, and lithium and indium metal foils are used as the counter electrodes. In these Figures 3A, 3B, 3C, and 3D, the rate performance is shown for Si anodes with various mass loadings, and 1C rate is defined as 3000mAh / g relative to the Si mass. [Figure 3D]3A, 3B, 3C, and 3D show three examples of electrochemical rate performance of single-sided silicon anode with various mass loading in solid-state half-cell. Argyrodite sulfide-based Li6PS5Cl is used as solid electrolyte layer, and lithium and indium metal foil is used as counter electrode. In these Figs. 3A, 3B, 3C, and 3D, rate performance is shown for Si anode with various mass loading, and 1C rate is defined as 3000mAh / g for Si mass. Indium metal is used to avoid parasitic reaction between lithium metal and solid electrolyte Li6PS5Cl. All-solid-state half-cell is tested to verify the feasibility of silicon film as anode in all-solid-state battery. Quite obviously, the results of the examples show that silicon anode of the present invention exhibits excellent lithium ion hosting ability in solid-state battery. [Figure 4] 1 shows an example of electrochemical cycling performance of a single-sided silicon anode in an all-solid-state half-cell, in which argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer and lithium and indium metal foils are used as the counter electrode. [Figure 5A] 1 shows two examples of electrochemical rate performance of a single-sided silicon anode according to the present invention in an all-solid-state battery, in which argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer and a lithium nickel manganese cobalt oxide mixture (LiNi0.6Mn0.2Co0.2O2, NMC622 cathode active powder mixed with Li6PS5Cl, and conductive carbon powder) is used as the cathode. [Figure 5B] 1 shows two examples of electrochemical rate performance of a single-sided silicon anode according to the present invention in an all-solid-state battery, in which argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer and a lithium nickel manganese cobalt oxide mixture (LiNi0.6Mn0.2Co0.2O2, NMC622 cathode active powder mixed with Li6PS5Cl, and conductive carbon powder) is used as the cathode. [Figure 6]1 shows an example of the electrochemical cycling performance of a single-sided silicon anode according to the present invention in an all-solid-state battery, in which argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer and a lithium nickel manganese cobalt oxide mixture (LiNi0.6Mn0.2Co0.2O2, NMC622 cathode active powder mixed with Li6PS5Cl, and conductive carbon powder) is used as the cathode. [Figure 7A] 1 shows an example of electrochemical cycling performance of a single-sided silicon anode according to the present invention in an all-solid-state battery, in which argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer, and lithium niobium oxide (LiNbO3)-coated lithium nickel manganese cobalt oxide (LiNi0.8Mn0.1Co0.1O2 coated with LiNbO3, NMC811 cathode active powder) mixed with Li6PS5Cl powder is used as the cathode (the mass ratio of NMC811:Li6PSCl5 in the example is 70:30 mass%). [Figure 7B] 1 shows an example of the electrochemical cycle performance of the single-sided silicon anode according to the present invention in an all-solid-state battery. Argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer, and lithium niobium oxide (LiNbO3)-coated lithium nickel manganese cobalt oxide (LiNi0.8Mn0.1Co0.1O2 coated with LiNbO3, NMC811 cathode active powder) mixed with Li6PS5Cl powder is used as the cathode (the mass ratio of NMC811:Li6PSCl5 in the example is 70:30 mass%). In this example of the all-solid-state battery, Argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer, and LiOH-treated LiNbO3-coated NMC811 mixed with Li6PSCl5 in a mass ratio of 70:30 mass% is used as the cathode. [Figure 8A]1 shows an example of the electrochemical cycle performance of the single-sided silicon anode according to the present invention in an all-solid-state battery, where the cathode active material LiNbO3 coating NMC811 is further processed by using LiOH by simply grinding and mixing LiOH powder and NMC811 powder in a certain mass ratio, and then the mixture is further annealed in air at a certain temperature. In this example, the mass ratio of LiOH:LiNbO3 coating NMC811 is 5:95 mass%, and then the mixture is annealed at 750°C for 10 hours in contact with air. [Figure 8B] 1 shows an example of the electrochemical cycle performance of the single-sided silicon anode according to the present invention in an all-solid-state battery, where the cathode active material LiNbO3 coating NMC811 is further processed by using LiOH by simply grinding and mixing LiOH powder and NMC811 powder in a certain mass ratio, and then the mixture is further annealed in air at a certain temperature. In this example, the mass ratio of LiOH:LiNbO3 coating NMC811 is 5:95 mass%, and then the mixture is annealed at 750°C for 10 hours in contact with air. [Figure 9][Fig. 9A] Schematic representation of a silicon anode material according to the invention for use in a lithium battery, where the anode structure is seen before lithiation. [Fig. 9B] Schematic representation of a silicon anode material according to the invention for use in a lithium battery, where the anode structure is seen after lithiation. [Fig. 9C] SEM images showing this effect on the actual tested material. On the current collector (1) nodules are added (2). In our case this is a copper foil with copper nodules, but this idea can be applied to different substrates. [Fig. 9D] SEM images showing this effect on the actual tested material. On the current collector (1) nodules are added (2). In our case this is a copper foil with copper nodules, but this idea can be applied to different substrates. [Fig. 9E] Distances and sizes of structures that define the average gap (a) between the nodules. The angle of initial growth is perpendicular to the basal plane, hence the starting average value for b (representing the outer cone angle β); the angle γ of the top of the columnar structure; the average height s of the structure are preferably in the range of 0.25 μm to 3 μm. It should be noted here that the height of the pillars depends on the mass loading, which is preferably about 1.5 mg / cm2 = 10 μm. The average radius of the columnar structure or nodule at its widest point is preferably in the range of 0.125 μm to 1 μm. The preferred average radius of the dome-shaped top of the columnar structure is preferably in the range of 0.1 μm to 5 μm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Unless otherwise defined, all technical and scientific terms herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. The terms used in the description of the present invention herein are merely for the purpose of describing the embodiments and are not intended to limit the present invention.
[0018] As used herein, the term "all-solid-state battery" refers to a silicon anode, a mixed cathode, and an argyrodite solid electrolyte layer therebetween.
[0019] The term "semi-solid battery" refers to a silicon anode, a mixed cathode, and a semi-solid electrolyte layer therebetween, the electrolyte including solid components in the form of, for example, a gel or wet sand.
[0020] As used herein, the term "silicon anode" refers to a silicon film deposited directly on one or both sides of a copper current collector.
[0021] The term "silicon film" as used herein refers to an amorphous porous silicon structure consisting essentially of silicon, with a plurality of pillars and nano-sized primary particles within the silicon pillars produced by a plasma enhanced chemical vapor deposition (PECVD) process.
[0022] The term "silicon film" herein refers to a layer of silicon, hydrogenated silicon, or doped silicon, either amorphous or crystalline, or a mixture of amorphous and crystalline.
[0023] The anode material is preferably i) a current collector material layer; ii) at least a first silicon layer deposited on the current collector material layer; and A composite electrode material comprising:
[0024] The silicon film or layer may comprise several different layers, preferably with a thickness of 5 to 50 μm and a density of 0.1 to 4 mg / cm 2 It should be noted that the thicknesses and mass loadings of the silicon films described herein are not limiting and can be thinner and lighter or thicker and heavier.
[0025] The term "amorphous silicon" as used herein is meant to include procrystalline silicon, which can be defined as amorphous silicon containing a proportion of nanocrystalline silicon, which may be up to about 30% of the nanostructured silicon layer.
[0026] An optional first silicon semicollector material layer and a surface area of one layer is in direct contact with a surface area of the other layer.
[0027] Any first silicon layer according to the present invention preferably has a low porosity, which allows the adhesion between the silicon active material and the current collector material layer to be increased, and also serves as a substrate for the adhesion of the second silicon layer to be increased.Thus, any first silicon layer may have a high porosity that reduces the increased adhesion.Preferably, any first silicon layer according to the present invention has a porosity of less than 30, 20, or 15%, more preferably less than 10, 9, 8, 7, or 6%, and most preferably less than 5, 4, 3, 2, or 1%.
[0028] The porosity of the silicon layer is generally determined by the Barrett-Joyner-Halenda (BJH) method according to ISO 15901-2:2006. ISO 15901-2:2006 describes a method for evaluating porosity and pore size distribution by gas adsorption, which is explained in more detail below. However, the silicon layer according to the present invention may comprise multiple layers with different porosity.
[0029] The production of the second silicon layer may require any first silicon layer as a substrate for its formation and specific structure. After the production of the composite electrode material, multiple silicon layers cannot be reliably separated without damaging or destroying the layer, thereby changing its porosity. Therefore, the BJH method (according to ISO 15901-2:2006) is not well suited to determine the exact porosity of each individual silicon layer of the composite electrode material when multiple silicon layers are present.
[0030] Analysis of cross-sectional electron microscopy images of the composite electrode material produced is preferred to determine the porosity of the individual silicon layers of the composite material according to the present invention. The analysis can be carried out by visual inspection of the image or automatically by using an image analysis algorithm configured to distinguish the silicon material from the void space in the silicon layer, for example via differences in pixel intensity using a suitable threshold. Thus, according to the present invention, the porosity of the silicon layer, preferably any first layer, second or additional layer, more preferably any first or additional layer, is preferably determined by electron microscopy.
[0031] Alternatively, analysis of cross-sectional electron microscopy images of a composite electrode material according to the invention can be advantageously combined with the BJH method according to ISO 15901-2:2006 to determine the porosity of multiple silicon layers, e.g. the first silicon layer and the second silicon layer according to the invention.
[0032] The data from the BJH method can be combined with an image analysis algorithm. For example, the BJH method is first used to measure the porosity of a composite electrode according to the present invention that includes multiple silicon layers. The algorithm can then determine the porosity of the silicon layers by analyzing cross-sectional electron microscopy images of the composite electrode according to the present invention that includes multiple silicon layers, and then compare the determined porosity with the historical data of the BJH method that was used to determine the specific porosity of a single silicon layer. The algorithm can then use the historical BJH data of the single layer to determine the porosity of multiple silicon layers, while also using the latest BJH data.
[0033] At least a second silicon layer according to the present invention is present or positioned on either any first silicon layer or on the current collector material layer, with a surface area of one layer directly contacting a surface area of the other layer.
[0034] At least the second silicon layer according to the present invention has a higher porosity than any first layer.When the first layer is not present, the second layer can have any porosity, but it is less than 80%.High porosity allows the silicon active material to have a larger volume expansion, resulting in less stress and less risk of breakage during lithiation and delithiation cycles.In addition, the lithium ion transport in the electrolyte phase is increased by the highly porous structure of the silicon layer.
[0035] Preferably, the second silicon layer according to the present invention has a porosity of more than 1,2,3,4,5,6,7,8,9 or 10%, more preferably more than 5,6,7 or 8%.A sufficient amount of silicon active material needs to be present for energy storage.Therefore, according to the present invention, the second silicon layer preferably has a porosity of 5,10 or 15 to 20,25,30,35,40,45,50,55,60,70 or 80%, more preferably 6,7,8,9 or 10 to 18,20,25 or 30%, most preferably 6 or 8 to 18%.
[0036] The second silicon layer according to the present invention preferably has a porosity ranging from a porosity higher than that of any first silicon layer to less than 80, 70, 60, 55, 50, 45, 40, 35, or 30%, more preferably less than 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, 20, or 19%, and most preferably less than 20 or 19%.
[0037] The porosity of the second silicon layer according to the invention can be determined by electron microscopy or by the BJH method according to ISO 15901-2:2006. The BJH method according to ISO 15901-2:2006 has the advantage of being a faster and less laborious analytical method than electron microscopy. The specific porosity percentage of the second or additional layer according to the invention can be determined by the BJH method according to ISO 15901-2:2006. Thus, the porosity of the second or additional silicon layer according to the invention can be determined by the BJH method according to ISO 15901-2:2006, which will be described in more detail below.
[0038] The porosity and (average) pore size of the material according to the invention are preferably determined using nitrogen gas according to the method specified by the ISO (International Organization for Standardization) standard: ISO 15901-2:2006 "Pore size distribution and porosity of solid materials by mercury porosimetry and gas adsorption - Part 2: Analysis of mesopores and macropores by gas adsorption". The specific surface area of the material according to the invention is preferably determined using nitrogen gas according to the method specified by the ISO standard: ISO 9277:2010 "Determination of the specific surface area of solids by gas adsorption - BET method". Briefly, for both ISO methods, the N2 adsorption-isotherm is measured at about -196°C (liquid nitrogen temperature).
[0039] The pore size and pore volume can be determined by the Barrett-Joyner-Halenda calculation method (Barrett, EP; Joyner, LG; Halenda, PP (1951), "The Determination of Pore Volume and Area Distributions in Porous Substances. I. Computations from Nitrogen Isotherms", Journal of the American Chemical Society, 73(1): 373-380). The specific surface area can be determined from the same isotherm by the Brunauer-Emmett-Teller calculation method (Brunauer, S.; Emmett, PH; Teller, E. (1938), "Adsorption of Gases in Multimolecular Layers", Journal of the American Chemical Society, 60(2): 309-319). Both calculation methods are well known in the art. A simple experimental test method for determining the isotherm can be described as follows: The test sample is dried at high temperature and under an inert atmosphere. The sample is then placed in the measurement apparatus. The sample is then placed under vacuum and cooled using liquid nitrogen. The sample is kept at liquid nitrogen temperature during the recording of the isotherm.
[0040] The term "void space" or "void structure" in this specification is understood to mean a silicon layer region that does not contain a component of the composite electrode. The void space or structure is empty or filled with an atmospheric (liquid or gaseous) fluid. The void space or structure provides a region for silicon to expand during use of the composite electrode material. Furthermore, an electrolyte, or an electrolyte containing lithium (ions), can be present in the void space or structure during use of the composite electrode material in a battery. The determination of the dimensions of the void space or structure is preferably performed by analysis of a cross-sectional image of the layer or material by electron microscopy, the cross section being perpendicular to the surface of the current collector material. The dimensions of the void space or structure are preferably determined by analysis of a cross-sectional image of the layer or material over a continuous region of the void space or structure.
[0041] At least the second silicon layer according to the invention preferably comprises a plurality of void structures having an average width of 1 to 10 nm. The additional silicon layer according to the invention may comprise a plurality of void structures having an average width of 1 to 10 nm. The presence of void structures in the additional silicon layer depends on the porosity of the additional silicon layer. Preferably, the void structures comprise elongated tubular structures, channels, and / or a plurality of interconnected pores. The void structures mostly have a substantially oblique orientation with respect to the normal angle to the surface of the current collector material, as can be determined from a cross-sectional electron microscope image perpendicular to the surface of the current collector material. Preferably, the void structures according to the invention have an average width of 1, 2, 3, 4, or 5 to 6, 7, 8, 9, or 10 nm. The void structures according to the invention may have a length up to the thickness of the silicon layer. Their width may vary along their length. Exemplary void structures are embodied in Figs. 2 and 3.
[0042] Preferably, the anode material according to the invention comprises an additional silicon layer present or positioned on top of the second silicon layer, optionally with one or more additional silicon layers each in turn present or positioned on the respective directly underlying additional silicon layer, each additional silicon layer having a porosity different from the porosity of the second silicon layer and / or the directly underlying additional silicon layer. According to the invention, the porosity of the silicon layers, preferably of any first, second or additional layers, more preferably of any first or additional layers, is preferably determined by electron microscopy.
[0043] At least a second silicon layer according to the invention can be a gradient layer, which has a first surface and a second surface opposite the first surface, and a porosity that varies with a distance defined from the first surface to a plane parallel to the first surface of the second layer, the maximum distance being the thickness of the gradient layer defined between the first and second surfaces. An additional silicon layer according to the invention can be a gradient layer, which has a first surface and a second surface opposite the first surface, and a porosity that varies with a distance defined from the first surface to a plane parallel to the first surface of the additional layer, the maximum distance being the thickness of the gradient layer defined between the first and second surfaces. Preferably, either the first surface or the second surface faces and contacts the first silicon layer. Preferably, the porosity varies from a minimum porosity at one of the first and second surfaces to a maximum porosity at the other of the first and second surfaces. Preferably the porosity decreases from one of the first and second surfaces to a value at a point between the first and second surfaces and increases from that value to the other of the first and second surfaces.
[0044] Preferably, the porosity increases from one of the first and second surfaces to a value at a point between the first and second surfaces and decreases from that value to the other of the first and second surfaces. Preferably, the point is a plane parallel to the first or second surface. Preferably, the point is at a distance of 5 to 95% of the maximum distance, the maximum distance being the thickness of the gradient layer defined between the first and second surfaces. More preferably, the point is at a distance of 20 to 80% of the maximum distance, more preferably at a distance of 30 or 40 to 60 or 70%. Preferably, the point is at a distance of about 10, 20, 30, 40, or 50% of the maximum distance.
[0045] It is understood that the preferred gradient layer according to the present invention does not have a clear boundary in the layer in terms of porosity, for example when evaluated via electron microscopy.When the difference in porosity is mentioned in terms of the different lower or higher porosity of the different silicon layers according to the present invention when compared with the silicon layer having a gradient layer, it is understood that this is compared with the average porosity of the silicon layer having a gradient layer.
[0046] A preferred multilayer configuration of the composite material according to the invention foresees a stack of silicon layers, each having a porosity different from that of the adjacent silicon layers. In such a configuration, the first, preferably bottom, surface area of the second silicon layer is in direct contact with the surface area of any first silicon layer, preferably opposite to the surface area in direct contact with the current collector material layer, and the second, preferably opposite, surface area of the second silicon layer is in direct contact with the first, preferably bottom, surface area of the additional silicon layer. Alternatively, the first, preferably bottom, surface area of the second silicon layer is in direct contact with the surface area of the current collector, and the second, preferably opposite, surface area of the second silicon layer is in direct contact with the first, preferably bottom, surface area of the additional silicon layer.
[0047] Furthermore, the first, preferably bottom, surface region of each of any one or more additional silicon layers is in direct contact with the second, preferably opposing, surface region of the respective directly underlying additional silicon layer. An example of a multilayer configuration is illustrated in FIG. 1. The composite material according to the invention preferably comprises multiple silicon layers formed such that layers with lower porosity and layers with higher porosity are stacked one on top of the other. The composite material according to the invention preferably comprises one or more silicon layers, preferably any first layer, second and / or additional silicon layers, on only one side of the current collector material or on each of both sides of the current collector material.
[0048] Advantageously, the composite material according to the invention has a combined thickness of preferably from 1 to 30 or 50 μm, preferably from 5 or 10 to 15 or 20 μm, or from 0.1 to 4 mg / cm 2 , preferably 0.5, 0.8, 1.0, 2.0 to 2.5, 3.5, or 4.0 mg / cm 2 The combined thickness or mass loading is for the silicon layer present on one side of the current collector material layer.
[0049] The term "argyrodite solid electrolyte layer" herein refers to an argyrodite sulfide-based electrolyte composed of PS4 3-, S2-, and halide anions and lithium cations (e.g., Li7P3S11, Li6PS5Cl, Li6PS5Br, etc.), where the layer is formed under pressure.
[0050] The term "mixed cathode" herein refers to a cathode active material, an argyrodite sulfide-based powder, and a conductive carbon material in a certain mass ratio. The cathode active material can be one or a combination of lithium nickel manganese cobalt oxide or lithium nickel cobalt aluminum oxide or lithium manganese spinel or lithium iron phosphate.
[0051] The argyrodite sulfide system is composed of PS4 3-, S2, and halide anions, and lithium cations (e.g., Li7P3S11, Li6PS5Cl, Li6PS5Br, etc.) The conductive carbon material is composed of one or a combination of carbon black, carbon nanofibers, or glassy carbon materials.
[0052] The anode material, and / or both the anode and cathode materials according to the present invention can be successfully used in solid or semi-solid electrolyte batteries. The subject batteries, particularly the anode materials, have a fully recoverable tensile elastic strain of 1% to 1000% and a maximum elastic strain of 10% when measured at room temperature using an anode protection layer in physical contact with the anode active material layer. -8 S / cm to 5×10 -2 It has also proven useful to use a semi-solid electrolyte without a porous separator disposed between the cathode and the anode, consisting of a polymer material with a lithium ion conductivity of 100 S / cm.
[0053] The silicon films according to the present invention are preferably designed to be used as anodes for semi-solid or solid state batteries.
[0054] For a solid-state battery, preferably, the battery comprises: (i) a 100% silicon layer composite with an amorphous structure; (ii) a porous silicon layer comprising a plurality of pillars and nano-sized primary particles in the silicon pillars; (iii) a copper current collector on which a silicon film is directly deposited; (iv) an argyrodite sulfide based electrolyte layer or pallet; and (v) a cathode mixture comprising one or a combination of lithium nickel manganese cobalt oxide or lithium nickel cobalt aluminum oxide or lithium manganese spinel or lithium ion phosphate cathode active materials, argyrodite sulfide based powder, conductive carbon material.
[0055] The silicon layer may advantageously comprise an amorphous structure in which nanocrystalline regions may be present.Furthermore, according to the present invention, the depletion of the amorphous structure leads to the formation of pores in the structure with nano-sized primary particles and pore sizes of 10-40 nm.The structure comprising a plurality of pillars also preferably exhibits a large porosity, preferably ranging from 10% to less than 80% porosity as determined by electron microscopy.
[0056] The advantage of this unique structured silicon anode is that the swelling behavior of the silicon anode can be limited during electrochemical lithiation.
[0057] The silicon anode, when used as an anode in a lithium ion battery, preferably comprises a metal or metal alloy, preferably copper, nickel, or titanium current collector. The silicon layer may further preferably have a thickness in the range of 1 μm to 30 μm. The silicon layer may further preferably have a thickness in the range of 0.25 to 4.0 mg / cm. 2 The mass load may be up to 1000 .mu.m.
[0058] As a result, the specific capacity of the silicon anode is up to 0.75 mAh / cm 2 to 12mAh / cm 2 can be reached.
[0059] A particular benefit of the use of silicon anodes in solid-state batteries according to the present invention is that a solid electrolyte interface (SEI) tends to form only between the silicon layer and the solid argyrodite sulfide-based electrolyte.
[0060] Without being bound to a particular theory, it is believed that the thus formed SEI can act as a lithium ion conductor and an electron blocker. Compared to conventional liquid electrolytes, it has been observed that the lithium ion transport and electron pathways change from three-dimensional (3D) to two-dimensional (2D) in silicon anode-based solid-state batteries. The silicon pillars can thereby act as tunnels to transport electrons and lithium ions. Furthermore, the SEI is not expected to form at the depth of the silicon layer since there is no direct contact with the electrolyte. Thus, lithium ion loss in the spontaneous formation of new SEI is omitted for silicon anodes of solid-state batteries during cycling.
[0061] Preferably, the solid electrolyte layer (ii) comprises an argyrodite sulfide based solid electrolyte.Preferably, the silicon composite anode material comprises a silicon film and a copper, nickel or titanium current collector.
[0062] Preferably, the cathode layer comprises a cathode active material selected from lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium manganese spinel, lithium iron phosphate, and a conductive carbon material.
[0063] Preferably, the silicon composite material consists essentially of silicon and exhibits an amorphous structure containing nanocrystalline regions.
[0064] Preferably, the silicon layer has a porous silicon structure with a plurality of pillars and nano-sized primary particles in the silicon pillars.
[0065] Silicon columnar structures may be arranged in various ways, typically with a central axis. However, these columnar structures may be arranged such that an angle is formed between the basal plane and the central axis. Without being bound to any particular theory, it is believed that this may be the result of nucleation and subsequent ballistic growth after deposition of more silicon. Depending on the surface roughness of the current collector material, the central axis of these structures may deviate from a strictly perpendicular position to the basal plane. When such growth occurs, a stacked cone shape, an ice cream cone shape, or an inverted stacked cone structure may be formed. The diameter of the structure may conveniently range from 10 μm to 200 μm, preferably from 80 μm to 120 μm, for example 100 μm. Despite these structural variations, silicon anode materials are generally suitable for use in the compositions of the present invention.
[0066] The laminated cone according to the invention generally essentially comprises a truncated cone-shaped body, converging from a closed anchoring point of the base surface and diverging upwards from there, with a cone angle α between 65° and 85°, preferably between 70° and 80°. The divergence from this tapered section may be essentially a cylindrical section, thus forming a columnar structure essentially perpendicular to the base surface, or a convex, dome-shaped end, with a given radius R, thus forming an "ice cream" front pointing away from the base surface, or a dendritic structure. The average distance from the anchoring point, where the structure contacts the base surface along the longitudinal axis of the base portion, to the most distal point of the base surface is in the range of 3 μm to 15 μm. Preferably, this average length is in the range of 4 μm to 10 μm, as estimated from the cross-section shown in the SEM image. The macroscopic structure of the silicon columnar structure is advantageously analyzed via SEM imaging. In the top view (FIG. 2A), a very compact columnar morphology is seen, with some pillar tips appearing bulkier than others. Preferably, the anode material according to the present invention comprises a double-sided physical vapor deposition (PVD), chemical vapor deposition (CVD), pulsed laser deposition (PLD), sputtering, and / or electrochemical spray deposition silicon anode on either side of an essentially planar current collector. The truncated cone-shaped structure may expand into an essentially cylindrical section to form a columnar structure essentially perpendicular to the base surface; or a convex, dome-shaped end with a given radius R, thus forming an "ice cream" front pointing away from the base surface.
[0067] Preferably, the average distance along the longitudinal axis of the basal portion from the anchoring point where the structure contacts the basal surface to a distal point of the basal surface is in the range of 3 μm to 15 μm, preferably in the range of 4 μm to 10 μm, as estimated from the cross-section shown in the SEM image.
[0068] The average diameter of the cone that comprises any columnar portion at its surface is in the range of 0.5 μm to 15 μm, preferably 1.0 μm to 10 μm, based on the widest point of the cone and averaging the cone measurements every 10 μm, as determined by SEM microscopy.
[0069] The "average length" and "average cone angle" in this specification refer to the average of silicon structures counted and measured per 10 μm, as determined from SEM microscopy images. Between the truncated cone structures, smaller inverted cone structures are usually formed, with the cone narrowing in the direction away from the base. Without being bound to any particular theory, it is believed that this may be the result of these structures being limited in growth by growing adjacent portions faster.
[0070] Without wishing to be bound by any particular theory, it is noted that the presence of such structures appears to improve the stability of the anode material, especially when undergoing volume changes during lithiation, thereby providing a more stable solid electrolyte interface and minimizing electrode fracture over time and under cycling, since the available space between the structures can expand and contract with limited frictional pressure built up between the structures, as compared to, for example, closely packed parallel columnar structures. Thus, the inventive material according to the invention contains, on average, at least one inverted cone or smaller cone per larger cone, and more preferably at least 2 to 5 inverted cones or smaller cones per larger cone structure.
[0071] Preferably, the porous silicon layer has a porosity, determined by electron microscopy, in the range of 5% to 80%.
[0072] Preferably the silicon film is deposited directly on the current collector, preferably by plasma enhanced chemical vapor deposition (PECVD) techniques.
[0073] Preferably, the silicon film is deposited on one or both sides of the current collector.
[0074] Preferably, the silicon film has a thickness of from 1 μm to 30 μm, preferably from about 5 μm to 20 μm. Preferably, the silicon film has a thickness of from 0.1 to a maximum of 4.0 mg / cm. 2 The mass loads range from
[0075] The surface roughness of the current collector appears to play a role here, with rougher surfaces and / or surfaces containing more artifacts appearing to promote less uniform growth and therefore growth in directions that are not essentially perpendicular to the basal plane; whereas less rough surfaces or surfaces containing fewer artifacts appearing to result in more uniform formation of parallel columnar silicon structures. This is embodied by the material according to the invention, for example, as shown in FIG. 2B, which shows two different surfaces of a copper foil and, as a result, two slightly different silicon columnar structure morphologies.
[0076] Figures 9A and 9B show schematic diagrams of silicon anode material according to the invention for use in lithium batteries, including those for solid electrolytes, where the anode structure is shown before (A) and after (B) lithiation. Figures 9C and 9D show SEM images showing this effect on the actual materials tested. On the basal surface of the current collector (1) are added nodules or agglomerates (2), for example a copper foil with copper nodules or agglomerates.
[0077] The nodules or agglomerates are then the starting points for the growth of silicon columnar structures or pillars (3), especially when PECVD techniques are used to grow them, however in addition to pure silicon other chemical contents may be included, such as silicon alloys, and other deposition techniques may be applied that are encompassed within the scope of the present invention.
[0078] The use of agglomerates or nodules, or more generally surface roughness that are typically at a certain distance from each other, inherently results in non-vertical pillar growth. The pillar size can be described by an inverted cone shape with a portion of a sphere at the top, such as an ice cream cone, or a dendritic shape, where the pillar distance at the basal interface is large compared to the pillar distance at the top of the pillar.
[0079] During lithiation in lithium battery applications, silicon anodes swell. Figure 9 shows the additional volume of the anode caused by swelling at (4). This swelling causes mechanical stress. The most vulnerable part of the pillar to mechanical stress is the part near the interface. Mechanical stress near the interface can cause delamination of the pillar and deactivate the complete pillar. This delamination reduces the life of the lithium battery.
[0080] Because the distance between the pillars in the present disclosure is large at the interface, the mechanical stress at the interface during lithiation is limited, improving the life of the lithium battery.
[0081] Figure 9E shows the distance and size of the structures, where the distance from the center of a nodule or columnar structure to a second nodule or columnar structure is determined on a cross section, where the average overall range is in the range of 0.25 μm to 1.25 μm, preferably 0.75 μm to 1.2 μm. The average gap (a) between the nodules is in the range of 0.1 μm to 1.5 μm.
[0082] The initial growth angle is perpendicular to the basal plane, so a starting average value for b (representing the outer cone angle) is difficult. When nodules start growing from the artifact on the basal plane, i.e. at a point on the face of the structure, the trajectory of growth that forms the structure is not essentially vertical. At these points, the average cone angle is equal to or greater than 45° and grows toward the face, but eventually tapers to a more vertical direction. The average cone angle β is therefore in the range of 60° to 85°, for example in the range of 65° to 80°.
[0083] Preferably, the angle γ at the top of the peak of the nodules or structures is in the range of 10° to 90°. The average height of the structures is preferably in the range of 0.25 μm to 3 μm. This results in a pillar height that depends on the mass loading, preferably about 1.5 mg / cm. 2 Note that this typically corresponds to a height of 10 μm.
[0084] The average radius of the columnar structures or nodules at their widest point is preferably in the range of 0.125 μm to 1 μm. The average radius of the top of the columnar structures, which are preferably dome-shaped, is preferably in the range of 0.1 μm to 5 μm.
[0085] Preferably, the solid electrolyte layer is a sulfide-based solid electrolyte, preferably argyrodite, Li 10 GeP2S 12 (LGPS), Li7P3S 11 (LPS); Bare and doped Li7La3Zr2O 12 (LLZO) garnet structure oxide; a halogenated solid electrolyte, a NASICON type phosphate glass ceramic, preferably (LAGP), an oxynitride, preferably lithium phosphate nitride or LIPON; and a polymer, preferably PEO or PVA, or any combination thereof.
[0086] Preferably, the cathode layer comprises a cathode active material, a solid electrolyte, a carbon conductive material, and an aluminum current collector.
[0087] Preferably, the cathode active material comprises lithium cobalt oxide, lithium nickel oxide, lithium nickel manganese cobalt oxide, or lithium nickel cobalt aluminum oxide, or lithium manganese spinel, or lithium iron phosphate. The cathode active material in this claim can be one material or any combination thereof.
[0088] Preferably, the carbon conductive material in the cathode layer comprises an electrically conductive material, a carbon black conductive material, a carbon nanofiber conductive material, a carbon nanotube material, a glassy carbon conductive material, or a graphene conductive material, or a combination thereof.
[0089] The present disclosure also relates to a method for assembling a silicon anode based solid state battery, the method comprising: (i) depositing a single or double sided silicon film on a current collector to form a silicon anode material; (ii) providing a solid electrolyte layer in contact with the silicon film; and (iii) providing a cathode layer in contact with the solid electrolyte layer.
[0090] Preferably, step (ii) is carried out by compressing a solid electrolyte powder onto the silicon anode film, thereby forming a solid electrolyte layer, or step (ii) is carried out by a film formation method including slurry coating, physical vapor deposition (PVD), chemical vapor deposition (CVD), pulsed laser deposition (PLD), sputtering, and / or electrochemical spraying.
[0091] The present invention also relates to the use of a silicon anode comprising an essentially pure amorphous silicon film deposited on a current collector and comprising a plurality of columnar structures in a solid-state battery.
[0092] The present invention further relates to the use of a silicon anode comprising an essentially pure amorphous porous silicon film deposited on a current collector and comprising a plurality of columnar structures in a solid-state battery.
[0093] The following non-limiting examples illustrate the invention. EXAMPLES
[0094] Solid-state batteries were fabricated, anode and cathode mixtures were prepared, and battery performance evaluations were performed as described herein below.
[0095] Silicon anode: A silicon layer was deposited on one side of a copper foil by PECVD, thereby creating an anode silicon electrode material. The composite electrode material was produced as follows: a roll of copper foil current collector material was fed into a deposition device that included an unwinding chamber, two deposition chambers, and a rewinding chamber. All these chambers were connected and operated under vacuum (0.05-0.2 mbar). The foil was transported by a system of pulling rolls and two heated drums that would control the temperature of the foil. A first and at least a second silicon layer were deposited on the substrate by plasma enhanced chemical vapor deposition at a substrate temperature of 100-300°C. In this process, magnetron radiation with a frequency of 2.45 GHz was used to excite a gas mixture containing silicon precursor gas and supporting gas. Silane (SiH4) was the source of silicon, whereas argon (Ar) and hydrogen (H2) were added to stabilize the plasma, affect the material structure, and improve the deposition rate. The gas was injected through a "gas shower" which distributes the gas evenly. Magnetron radiation was introduced into the vacuum chamber by means of an antenna. To homogenize the plasma, both sides of the antenna are connected to the magnetron radiation source. Thus, magnetron heads are positioned on both sides. These magnetron heads are connected to the antenna. The gas is injected through a gas shower between the magnetron heads. The antenna is protected from the reactive environment by a quartz tube. The plasma is confined by a magnetic field generated by an array of permanent magnets. The silicon production rate was determined by the process conditions, the power input per source, and by the number of microwave sources in operation. The gas flow corresponded to a MW power input, which was between 800 and 6000 W / m. Ten antennas or sources of power input were used. Figures 2A and 2B show examples of top and cross-sectional SEM images of single-sided deposited silicon anodes prepared by this technique. Figure 2C shows an example of a cross-sectional SEM image of a double-sided deposited silicon anode. Of note in all figures are columnar structures which may include essentially parallel columnar structures but may be arranged such that an angle is formed between the base plane and the central axis of the column, such shapes are also typically referred to as stacked cones, ice cream cones, or stacked cone structures.The diameter of the as-laminated cones and / or ice cream cones can range from 1 to 10 μm.
[0096] Cathode Material The positive electrode mixture powder was prepared by mixing the active material powder, the solid electrolyte powder, and the conductive support material powder in a ball mill.
[0097] Example 2 Formation of solid-state batteries On top of the silicon anode material, a 2 μm thick layer of solid electrolyte argyrodite sulfide-based Li6PS5Cl was deposited as the solid electrolyte layer. To form the cathode, a paste of spherical particles and a suitable binder was made and pasted on top of the solid electrolyte. An indium foil was placed on top of the cathode to encapsulate the cell. The above example formed a battery structure as illustrated in FIG. 1.
[0098] Example 3 Solid-state battery performance The performance of the cells was tested, and Figures 3A, 3B, 3C, and 3D show three examples of electrochemical rate performance of single-sided silicon anodes with different mass loadings in solid-state half-cells, where Argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer, and lithium and indium metal foils are used as the counter electrode. In these Figures 3A, 3B, 3C, and 3D, the rate performance is shown for Si anodes with different mass loadings, and the 1C rate is defined as 3000 mAh / g relative to the Si mass. Indium metal was used to avoid or reduce parasitic reactions between lithium metal and the solid electrolyte Li6PS5Cl. The solid-state half-cells were tested to verify the feasibility of silicon structures as anodes in this solid-state battery. In the illustrated solid-state battery examples, Argyrodite sulfide-based Li6PS5Cl was used as the solid electrolyte layer.
[0099] The results show that the battery using the silicon anode according to the present invention performed extremely well, indicating excellent lithium ion hosting capability in a solid state battery.
[0100] FIG. 4 shows an example of the electrochemical cycling performance of a single-sided silicon anode in a solid-state half-cell, where argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer and lithium and indium metal foils are used as the counter electrode.
[0101] 5A and 5B show two examples of the electrochemical rate performance of single-sided silicon anodes in solid-state batteries, where argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer and a lithium nickel manganese cobalt oxide mixture (LiNi 0.6 Mn 0.2 Co 0.2 O2, NMC622 cathode active powder mixed with Li6PS5Cl, and conductive carbon powder) are used as the cathode.
[0102] FIG. 6 shows an example of the electrochemical cycling performance of a single-sided silicon anode according to the invention in a solid-state battery, in which an argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer and a lithium nickel manganese cobalt oxide mixture (LiNi 0.6 Mn 0.2 Co 0.2 O2, NMC622) cathode active granular material was mixed with Li6PS5Cl and conductive carbon powder was used as the cathode material.
[0103] FIG. 7 shows an example of the electrochemical cycling performance of a single-sided silicon anode according to the invention in a solid-state battery, in which an argyrodite sulfide-based Li6PS5Cl is used as the solid electrolyte layer and a lithium nickel manganese cobalt oxide (LiNbO3-coated LiNi 0.8 Mn 0.1 Co 0.1 % by weight with Li6PSCl5.
[0104] Figure 8 shows an example of electrochemical cycle performance of the single-sided silicon anode according to the present invention in a solid-state battery, where the cathode active material LiNbO3-coated NMC811 material is further processed by using LiOH, by simply grinding, and by mixing LiOH powder with NMC811 powder in a certain mass ratio, so that the mixture is further annealed in air at a certain temperature. In this example, the mass ratio of LiOH:LiNbO3-coated NMC811 is 5:95% by mass, and then the mixture is annealed at 750°C for 10 hours in contact with air.
[0105] As described above, according to exemplary embodiments of the present invention, the solid-state battery containing the inorganic nano-solid electrolyte has substantially improved battery performance as well as excellent safety, and can be widely used and involved in the development of industries such as electric vehicles or the like in which medium and large-sized lithium-ion rechargeable batteries are used.
[0106] Although the present invention has been described with reference to exemplary embodiments and the accompanying drawings, the present invention is not limited thereto, and various modifications and changes may be made by those skilled in the art to which the present invention pertains without departing from the scope of the present invention as set forth in the following claims. Further modifications and alternative embodiments of various aspects will become apparent to those skilled in the art in view of this description. This description is therefore to be construed as merely illustrative. It should be understood that the forms shown and described herein are to be construed as examples of embodiments. Elements and materials may be substituted for those shown and described herein, parts and processes may be reversed, and certain features may be utilized independently, all as may become apparent to those skilled in the art after having the benefit of this description. Changes may be made in the elements described herein without departing from the spirit and scope as set forth in the following claims. [Explanation of symbols]
[0107] 1 Copper foil, current collector 2 Silicon film, nodules 3. Solid electrolyte layer, silicon column structure 4 Cathode mixture layer, additional volume anode 5 Cathode current collector
Claims
1. a silicon anode comprising an essentially pure amorphous porous silicon film deposited on a current collector and comprising a plurality of columnar structures; an electrolyte layer comprising one or more solid components; A cathode layer; and Including, lithium-ion battery.
2. 10. The battery of claim 1, wherein the electrolyte layer comprises an argyrodite sulfide-based electrolyte.
3. 3. The battery of claim 1 or 2, wherein the silicon anode material comprises a silicon film and a copper, nickel, or titanium current collector.
4. 4. The battery of claim 1, wherein the cathode layer comprises a cathode active material selected from lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium manganese spinel, lithium transition metal oxide, lithium iron phosphate, or a combination thereof, and a conductive carbon material.
5. 5. The battery of claim 1, wherein the silicon anode material consists essentially of silicon and exhibits an amorphous structure containing nanocrystalline regions.
6. 6. The battery of claim 1 , wherein the silicon anode material has a porous silicon structure having a plurality of pillars and nano-sized primary particles in the silicon pillars.
7. 7. The battery of claim 6, wherein the silicon layer has a porosity in the range of 5% to 80% as determined by the PECVD deposition conditions.
8. 8. The battery of claim 1, wherein the silicon film is directly deposited on the current collector, preferably by plasma enhanced chemical vapor deposition (PECVD).
9. 9. The battery of claim 8, wherein the silicon film is deposited by a physical vapor deposition (PVD) method, such as a plasma-enhanced chemical vapor deposition (PECVD) method, a chemical vapor deposition (CVD) method, a pulsed laser deposition (PLD) method, sputtering, and / or an electrochemical spray method.
10. 10. The battery of claim 1, wherein the silicon film can be deposited on one or both sides of the current collector.
11. 11. The battery of claim 1, wherein the silicon film has a thickness of from 1 μm to 30 μm.
12. The silicon film is preferably about 5 μm to 20 μm thick and / or 0.1 to 4.0 mg / cm 2 12. The battery of claim 1 having a mass loading of up to 1000 .mu.m.
13. The electrolyte layer is a sulfide-based electrolyte, preferably argyrodite, Li 10 GeP 2 S 12 (LGPS), Li 7 P 3 S 11 (LPS), bare and doped Li 7 La 3 Zr 2 O 12 13. The battery according to any one of claims 1 to 12, comprising an electrolyte selected from a (LLZO) garnet structure oxide, a halide electrolyte, a NASICON type phosphate glass ceramic, preferably (LAGP), an oxynitride, preferably lithium phosphate nitride, or LIPON, and a polymer, preferably PEO or PVA, or any combination thereof.
14. 14. The battery of claim 1, wherein the cathode layer comprises a cathode active material, a solid electrolyte powder, a carbon conductive material, and an aluminum current collector.
15. 15. The battery of claim 13 or 14, wherein the cathode active material comprises lithium cobalt oxide, lithium nickel oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium manganese spinel, lithium iron phosphate, or a combination thereof.
16. 16. The battery of claim 14 or 15, wherein the carbon conductive material in the cathode layer comprises an electrically conductive material, a carbon black conductive material, a carbon nanofiber conductive material, a carbon nanotube material, a glassy carbon conductive material, or a graphene conductive material, or a combination thereof.
17. The cathode material is lithium niobium oxide (LiNbO 3 Lithium nickel manganese cobalt oxide, preferably granular LiNbO 3 LiNi coated with 0.8 Mn 0.1 Co 0.1 O 2 (NMC811) material, 6 P.S. 5 Cl granular material, more preferably NMC811:Li 6 PSC 5 17. The battery of claim 13, comprising a mixture of these in a mass ratio ranging from 90:10 to 60:40, more preferably in the range of 80:20 to 65:35 mass %.
18. Cathode LiNbO 3 Coated LiNi 0.8 Mn 0.1 Co 0.1 O 2 20. The battery of claim 17, wherein the (NMC811) material is further blended with LiOH while grinding, and then the mixture is annealed in the presence of air.
19. LiOH: LiNbO 3 19. The battery of claim 18, wherein the proportion of coated NMC811 is in the range of 1:99 to 10:90% by weight, preferably in the range of 3:97 to 7:93% by weight.
20. 20. The battery of claim 18 or 19, wherein the blended cathode material is annealed in the presence of air at a temperature in the range of 700° C. to 800° C., such as in the range of 725° C. to 775° C., for a period in the range of 1 to 20 hours, such as in the range of 8 to 12 hours.
21. Argyrodite sulfide Li 6 P.S. 5 Cl represents the solid electrolyte layer, and LiNbO 3 Coated LiNi 0.8 Mn 0.1 Co 0.1 O 2 (NMC811) material is Li 6 P.S. 5 21. The battery of claim 18, wherein the lithium ion battery is blended with CrCl in a mass ratio of about 70:30 mass% and used as a cathode material.
22. 1. A method for assembling a silicon anode based solid state battery, comprising: (i) depositing a single-sided or double-sided silicon film onto a current collector to form a silicon anode material; (ii) providing an electrolyte layer in contact with the silicon film; (iii) providing a cathode layer in contact with the electrolyte layer; A method comprising:
23. 23. The method of claim 22, wherein step (ii) is performed by compressing an electrolyte powder onto the silicon anode film, thereby forming a solid electrolyte layer, or step (ii) is performed by a film formation method including slurry coating, physical vapor deposition (PVD), chemical vapor deposition (CVD), pulsed laser deposition (PLD), sputtering, and / or electrochemical spraying.
24. 1. Use of a silicon anode in a solid-state battery, the silicon anode comprising an essentially pure amorphous porous silicon film deposited on a current collector and comprising a plurality of columnar structures.
25. 1. An anode material for use in a battery, preferably a solid-state battery, comprising: (i) a silicon anode comprising an essentially pure amorphous porous silicon film deposited on a current collector and comprising a plurality of columnar structures, the plurality of columnar structures being frustum-shaped structures converging from a closed anchoring point at a basal surface and diverging upward therefrom, with an average cone angle α in the range of 60° to 85°, for example 70° to 80°.
26. 26. The anode material of claim 25 comprising a double-sided silicon anode material deposited by physical vapor deposition (PVD), chemical vapor deposition (CVD), pulsed laser deposition (PLD), sputtering, and / or electrochemical spraying on either side of an essentially planar current collector.
27. 27. The anode material according to claim 25 or 26, wherein the frustoconical structures expand into essentially cylindrical sections forming columnar structures essentially perpendicular to the basal plane.
28. 28. The anode material of any one of claims 25 to 27, wherein the frusto-conical structure flares out into an essentially convex dome-shaped end having a given radius R, thus forming an "ice cream" front pointing away from the base surface.
29. 29. An anode according to any one of claims 25 to 28, wherein the average distance from the anchoring point where the structure contacts the basal surface along the longitudinal axis of the basal surface to a distal point of the basal surface is in the range of 3 μm to 15 μm, such as in the range of 4 μm to 10 μm, as estimated from a cross-section shown in a SEM image.
30. 30. An anode according to any one of claims 25 to 29, wherein the average distance of the cone or columnar portion which corresponds to the radius of the columnar portion is in the range of 0.5 μm to 15 μm, for example 1.0 μm to 10 μm, based on the widest part of the cone and averaged over measurements of the cone every 10 μm, determined by SEM microscopy.
31. 31. A rechargeable lithium ion battery comprising the anode material of any one of claims 25 to 30.
Citation Information
Patent Citations
Battery material and preparation method thereof
EP3876311A1
Lithium oxide argyrodites
US20200087155A1
All-solid secondary battery
US20210143413A1